Tissue culture response of different wheat genotypes, environmental effect and association with plant traits - Dodig D.; Nikolic R.; Mitic N. (Cereal science and technology for feeding ten billion people: genomics era and beyond, 2008)
The tissue culture response of immature embryos of 96 bread wheat genotypes was evaluated by measuring the percentage of callus formation (CF), the percentage of calli with regenerative potential (RC), and the average number of plants per regenerating embryo (PPE). The results showed great variability for RC among tested genotypes and strong genotype effect on this trait. Correlation analysis revealing positive and significant relationship between CF and early vigour, peduncle length, peduncle extrusion, spike index and yield per plant, as well as RC and PEE with chlorophyll content in flag leaf.
Meeting of the Eucarpia Cereal Section, 2006/11/13-17, Lleida (Spain)